ANALISIS PANDANGAN MASYARAKAT UMUM TERHADAP ADANYA PRAKTIK KONVENSIONAL PERBANKAN SYARIAH DI KOTA MAKASSAR - -, Hasanuddin; Wahyuni, Idra (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2018)
The shaking of Islamic banks was increasingly felt after the monetary crisis in 1998 with the presence of many conventional banks opening sharia bank branches. But ironically, even though the Indonesian people are Muslim majority, they have not shown a good view of the presence of Islamic banks. This study aims to examine the public's view of the conventional practice of Islamic banking in the city of Makassar on Islamic banking products in the form of murabahah, musyarakah, and mudaraba. Sampling was done through a purposive sampling approach, namely the customers of Islamic banks in Makassar City and the measurement of samples using dummy measurements. The testing method for the variable X1 (murabahah), variable X2 (musyarakah), and variable X3 (mudaraba) is done using logistic regression techniques through five stages of testing. The test results found that the views of the Makassar City community towards the existence of conventional Islamic banking practices on sharia banking products in the form of murabahah and mudaraba were not suitable. Whereas the sharia banking product in the form of musharaka is appropriate